An Analysis on The Teacher’s Oral Feedback in Teaching English : (A Descriptive Qualitative Research at SMK Negeri 6 Pontianak in Academic Year 2022/2023) - Nurul Puspitasari; Regina; Dwi Riyanti; Rahayu Apriliaswati; Eni Rosnija (Kirana Publisher (KNPub), 2023)
Feedback is one of the important components in the teaching and learning process. Feedback given by the teacher can make the teaching and learning process more effective. The teacher can optimize the learning process by giving feedback so students can understand the material better. Feedback can make students know their weaknesses and strengths so they can learn from there and evaluate themselves. This study focused on the types of oral feedback the teacher gave in teaching English at SMKN 6 Pontianak, especially in teaching students' speaking skills in class XI. This study aims to determine the types of oral feedback the teacher uses to teach speaking skills and find out the most frequently used oral feedback. The researcher conducted classroom observations and teacher interviews to collect data, which were then analyzed using the interactive model from Miles, Huberman, and Saldaña (2014). Based on classroom observations and teacher interviews, the researcher found that the teacher used positive and corrective oral feedback to teach students' speaking skills. Positive oral feedback was given in the form of reinforcement 22 times (46.81%) and evaluative nine times (19.15%), which totalled 31 times (65.96%). Other than that, corrective oral feedback was given in three different ways: recast 10 times (21.28%), elicitation three times (6.38%), and request for clarification three times (6.38%). Overall, the teacher gave oral corrective feedback 16 times (34.04%). From all types of oral feedback, it can be concluded that the most frequently used oral feedback by the English teacher at SMKN 6 Pontianak is positive oral feedback. While the most frequently used oral corrective feedback is recast.